PMO-255 The expression of interleukin 2 receptor in intestinal resection specimens from patients with Crohn's disease as assessed by immunohistochemistry. (28th May 2012) - Russo, E; Petts, G; Lloyd, T; Goldin, R; Matthews, P; Orchard, T
Abstract : Introduction: Interleukin-2 (IL-2) is a key cytokine in inflammatory pathways involving T-cells. Several studies assess the potential of IL-2 scintigraphy to quantify T-cell infiltrates in conditions such as diabetes, coeliac and Crohn's Disease (CD). To assess the potential utility of IL-2-based Positron Emission Tomography (PET) radio-ligands that target the IL-2 receptor (IL-2R) in Crohn's disease imaging, we examined the differential expression of the α-subunit of the IL-2R (CD25) in intestinal resection specimens from patients with CD. Methods: Stored, formalin-fixed paraffin-embedded blocks from Crohn's intestinal resection specimens were retrieved. Four 1μm-thick consecutive sections from each block were stained with H&E and CD25 (CD25 1:100, Leica NCL-CD25:305). A pathologist carried out a semi-quantitative grading of acute and chronic inflammation from H&E stained slides attributing a score of 0–3 for each of the two components. Their sum represented the Global Inflammatory Score (GIS). Specimens were subcategorised on the basis of GIS into Group A (GIS 0–1, no or mild inflammation), Group B (GIS 2–4, moderate) and Group C (GIS 5–6, severe). While blinded to the GIS, the pathologist quantified CD25 expression by counting CD25+ve cells in 1mm-wide full thickness regions of bowel wall on slides containing complete, well-orientated mucosa, submucosa and muscularis propria. Results were expressed as CD25+ve cells/mm 2 . Groups were compared using the Mann–Whitney test. In addition, qualitative co-localisation studies of CD25 and CD3 (CD3 1:50 Leica NCL-L-CD3-565) or CD45 (CD45 1:100 Dako M0701) were performed on a sub-selection of six slides. Results: 12 sets of slides were produced from five resection specimens. A median of 3 (range 2–6) 1 mm wide well orientated bowel wall regions were scored on each slide (total 41). Of these, 15 (37%) were in Group A, 12 (29%) in Group B and 14 (34%) in Group C (see above). Median CD25+ve cell count per mm 2 was 2.04 (range 0.32–6.94), 2.74 (range 0.97–13.86) and 8.89 (range 2.14–59.66) respectively. CD25 was significantly more abundant in Group C than in Group A (p=0.0005) and Group B (p=0.019). The difference in CD25 expression between Groups A and B did not reach statistical significance (p=0.08). Co-localisation studies of CD25 and CD3 or CD45 suggest that the majority, but not all CD25 expression occurs on leucocytes (CD45 positive cells) and specifically T-lymphocytes (CD3 positive cells). Conclusion: IL2R was significantly more abundant in areas with a severe inflammatory infiltrate, therefore 18F-IL2 PET scanning could be useful in delineating such areas. CD25 appears predominantly but not exclusively expressed on T-cells. Competing interests: None declared.